The effect of cacao bean extracts on the prevention of periodontal tissue breakdown in diabetic rats with orthodontic tooth movements - Nuzulul Hikmah; Mohamad Hidayat; Nur Permatasari; Aulanni'am Aulanni'am; Achmad Rudijanto (Journal of Oral Biology and Craniofacial Research)
Objective: Proper management of orthodontic treatment in diabetic patients is essential due to the heightened risk of periodontal tissue breakdown associated with hyperglycemia. Cacao bean extracts (CBE) are known to reduce the inflammatory response and increase synthesis and angiogenesis in periodontitis. Therefore, this study aims to examine the effect of CBE on preventing periodontal tissue breakdown in diabetes with orthodontic force. Methods: A total of 25 Wistar rats were divided randomly into 5 groups, including non-diabetes, diabetes, diabetes cacao 125, 250, and 500 mg/kg BW. Diabetic rats were induced with the stratified dose of Streptozotocin, and a 30-g-force from orthodontic device was applied in all groups. Diabetes cacao group was given CBE for 7 days using a gastric probe. GCF samples were used to analyze the eNOS level through the ELISA method. NFκB, Collagen-1, and FGF-2 expression were then assessed using the immunohistochemical method, while the number of fibroblasts and blood vessels was observed using hematoxylin-eosin stained tissue. The data obtained were analyzed with one-way ANOVA and post hoc tests, with p < 0.05. Results: CBE at a dose of 250 mg/kg BW significantly increased eNOS level, Collagen-1, and FGF-2 expression, and the number of fibroblasts and blood vessels in diabetes groups. Meanwhile, the treatment decreased NFκB expression in diabetes groups (p < 0.05). Conclusion: This study proved that CBE increased periodontal ligament synthesis and angiogenesis and decreased inflammatory response, thereby preventing periodontal tissue breakdown in diabetic rat models with tooth movement.